(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2017)
Beauty and its refusal are not merely a cipher of contemporaneity but a topic discussed since antiquity. The rivalry between lyre and flute, between harmony, mathematically determinable, and melody, gatherable only by hearing, arises from the myth, from the fight between Apollo and Marsia, where Greece and Phrygia, Europe and Asia are opposed in a civilisations collision. In modernity this collision arose again as political, whereas the egalitarian melody is opposed to the elitist harmony. Into this collision we find fine arts, not beauty anymore: fine arts leave the territory of beaux arts of fine poetry but remain, for contemporaneity, works of art. But what do arts, not beauty anymore, or even ugly, want? Which aim do they pursue? How can we judge them?